A Comparison of Hay and Fish Emulsion-Infused Water as Oviposition Attractants for the CDC Gravid Trap. Issue 2 (20th December 2021) - McNamara, Timothy D; Healy, Kristen
Abstract: Multiple oviposition attractants are used for Culex (Diptera: Culicidae) mosquito surveillance in the CDC Gravid Trap, including hay and fish emulsion-infused water. Despite the use of both in the United States, no research has compared their attractiveness. We conducted trapping throughout Louisiana to assess the attractiveness of hay and fish emulsion-infused water in various habitat types and climates. Our results indicate that fish emulsion-infused water attracts more mosquitoes overall, more Culex quinquefasciatus (Say, 1823), and a wider diversity of mosquitoes than hay-infused water. This trend was maintained, regardless of habitat type or climate.